Identification of SHANK2 Pathogenic Variants in a Chinese Uygur Population with Schizophrenia - Zhang, Han; Wang, Dong; Chen, Jianhua; Li, Xiuli; Yi, Qizhong; Shi, Yongyong (Journal of molecular neuroscience, 2021)
Genomic studies on schizophrenia (SCZ) have revealed several candidate genes involved in excitatory synapse function and plasticity associated with its etiology. SHANK2 is a postsynaptic scaffolding protein, which anchors a protein complex connecting NMDAR, AMPAR, and mGluR receptors at excitatory neuronal synapses. Mutations in the SHANK2 gene have been reported to be associated with human autism spectrum disorders (ASDs) and SCZ. To identify variants in the SHANK2 gene and determine the association of SHANK2 with SCZ in the Chinese Uygur population, we conducted targeted sequencing of whole exon regions and exon-intron boundaries of SHANK2 in 1574 SCZ patients and 1481 healthy controls. A total of 149 variants were identified, including six common variants and 143 rare variants. For common variants, rs62622853 and rs3924047 showed allelic significance with SCZ before correction, but the association was eliminated after Bonferroni correction. Seven rare nonsynonymous variants, p.Arg739Trp, p.Pro807Leu, p.Ile854Phe, p.Thr1322Ser, p.Leu1434Arg, p.Val1486Ile, and p.Thr1674Met, occurred only in the patients but not in any of the healthy controls. In silico analysis predicted that p.Arg739Trp, p.Leu1434Arg, and p.Val1486Ile variants are likely to be damaging. The present study suggests that individuals with two novel rare nonsynonymous variants (p.Arg739Trp, p.Leu1434Arg) and p.Val1486Ile variants of SHANK2 might increase the susceptibility to developing SCZ disorder.